2012
DOI: 10.22401/jnus.15.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Influencing the Prevalence of Gairdia lamblia and Entamoeba histolytica in a Sample of Patients in North of Baghdad

Abstract: Different factors were examined related with the prevalence of Giardia lamblia and Entamoeba histolytica infections in population live north of Baghdad which were (seasonal tendency, travelling history and source of drinking water) during the period April 2009 till the end of March 2010. The study revealed that the total rate of parasitic protozoan infection (G.lamblia and E. histolytica) was (15.33%) , the infectiion rate of G.lamblia was higher than the infection rate of E.histolytica as their rates were (11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Among all items of general knowledge part, item 3"the disease occurred in human and some animals "showed high percentage (83.77%) of true response while item 10 "the disease found in our country" and item 6 " Sign and Symptoms of the dieses appear after 2-15 days" showed the lower percentages of true response which were (64.65%) and (63.51%) respectively. this low percentage may due to the following : the limitation of medical data base deal with this disease in Iraqi official websites (Universities , Ministry of health , Ministry of higher education and some researches institutes) ,not all of the Iraqi medical and scientific journal are available on the internet although there were several studies deal with cryptosporidiosis in Iraq [4,5,6,7,8,9] , limitation of mass media (such as television, radio, magazine, and newspaper) programs that deal with this disease in our country although some articles suggested that mass media, are not a very important source of information for some parasitic disease [13,14] , while the low percentages showed in item 6 because the clinical and epidemiologic significance of various Cryptosporidium species and genotypes in humans is not yet clear [15]. Results also showed significant differences (p< 0.05) between three groups in all items of general knowledge part except item 7 "the major clinical symptoms is diarrhea" , because diarrhea is the symptom of most gastrointestinal parasites such as Giardia lamblia and Entamoeba histolytica [16] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among all items of general knowledge part, item 3"the disease occurred in human and some animals "showed high percentage (83.77%) of true response while item 10 "the disease found in our country" and item 6 " Sign and Symptoms of the dieses appear after 2-15 days" showed the lower percentages of true response which were (64.65%) and (63.51%) respectively. this low percentage may due to the following : the limitation of medical data base deal with this disease in Iraqi official websites (Universities , Ministry of health , Ministry of higher education and some researches institutes) ,not all of the Iraqi medical and scientific journal are available on the internet although there were several studies deal with cryptosporidiosis in Iraq [4,5,6,7,8,9] , limitation of mass media (such as television, radio, magazine, and newspaper) programs that deal with this disease in our country although some articles suggested that mass media, are not a very important source of information for some parasitic disease [13,14] , while the low percentages showed in item 6 because the clinical and epidemiologic significance of various Cryptosporidium species and genotypes in humans is not yet clear [15]. Results also showed significant differences (p< 0.05) between three groups in all items of general knowledge part except item 7 "the major clinical symptoms is diarrhea" , because diarrhea is the symptom of most gastrointestinal parasites such as Giardia lamblia and Entamoeba histolytica [16] .…”
Section: Resultsmentioning
confidence: 99%
“…In Iraq, however there is several epidemiological studies deal with Cryptosporidiosis [4,5,6,7,8,9], It has been suggested, but not documented, that medical persons are generally unaware of this disease as well as a literature search has revealed no data about the degree of awareness about Cryptosporidium infections among Iraqis. So the aim of this study is to assess some medical person awareness of cryptosporidiosis and knowledge of some topics deal with this disease.…”
Section: Knowledge and Awareness Towardsmentioning
confidence: 99%
See 2 more Smart Citations
“…E. histolytica are often spread by contaminated food and/or drinking water and possibly from person to person through fecal oral contact [17]. Many papers reported different prevalence rates of E. histolytica in Iraq [18,19],but little is known about its relation to anemia, especially in children. The aim of this study was to determine the possible correlation between anemia and parasitic intestinal infection with E.histolytica.…”
Section: Introductionmentioning
confidence: 99%